Analisis Nilai-Nilai Spiritual Dan Pencarian Jati Diri Dalam Cerpen “Perjalanan Mengejar Cahayamu” Karya Shofa Zakia Ulfah - Muhammad Husain Abul Fidaa’ Fitono; Khoiroh, Nanik; Noor Azha, Salma Arsyadani (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study analyzes spiritual values and the search for identity in the short story Perjalanan Mengejar Cahayamu (The Journey to Pursue Your Light) by Shofa Zakia Ulfah, which is included in the short story collection published by Dakwahpos Publishing in 2018. Using a descriptive qualitative approach with a heuristic and hermeneutic reading model, this study explores religious symbols, narrative structures, and representations of the main character’s inner experiences. The results of the analysis show that the short story depicts a journey toward spiritual enlightenment through the symbol of light as a metaphor for finding meaning in life. Intrinsic elements of the story, such as plot, characters, and setting, are combined with socio-cultural dimensions that reflect the process of human inner transformation in finding peace, faith, and spiritual identity. This work emphasizes that the search for true identity is rooted in spiritual awareness that grows from existential experiences and closeness to divine values.